The story of painting : how art was made - Graham-Dixon, Andrew; Wilkes, Angela (Dorling Kindersley Limited, 2019)
"Covering a comprehensive array of topics, from the first pigments and frescos to linear perspective in Renaissance paintings, the influence of photography, Impressionism, and the birth of modern art, The Story of Painting follows each step in the evolution of painting over the last 25,000 years, from the first cave paintings to the abstract works of the last 150 years. Packed with lavish color reproductions of paintings and photographs of artists at work and the materials they used, it also focuses on key paintings from each period to analyze the techniques and secrets of the great masters in detail."--Publisher's description.